2020
DOI: 10.21608/asnj.2020.90524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stretching Exercise on Primary Dysmenorrhea among Secondary Girl Students at Assiut City

Abstract: Primary dysmenorrhea is common problem among adolescent which can have negative effects on their daily activities .Aim: to evaluate the effect of stretching exercise on primary dysmenorrhea among secondary girl students at Assiut city. Subject and Methods: Quazi experimental research design was used in this study included 666 students, while the students having dysmenorrhea 515 were selected by using multi stage random sample and the program implement on169 students from Assiut city. Through a period from Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…They found a statistically significant difference in the severity of dysmenorrhea among students who actively engaged in stretching exercises. They recommended incorporating educational courses on the benefits of such exercises into school curricula to increase students' awareness [18]. In the present study, a significant difference in baseline dysmenorrhea level was reported based on age and leave taken due to dysmenorrhea, which is consistent with the findings of Al-Matouq et al [19].…”
Section: Discussionsupporting
confidence: 91%
“…They found a statistically significant difference in the severity of dysmenorrhea among students who actively engaged in stretching exercises. They recommended incorporating educational courses on the benefits of such exercises into school curricula to increase students' awareness [18]. In the present study, a significant difference in baseline dysmenorrhea level was reported based on age and leave taken due to dysmenorrhea, which is consistent with the findings of Al-Matouq et al [19].…”
Section: Discussionsupporting
confidence: 91%